Microbial community structure and diversity of leaf phyllosphere in tobacco plants infected with wildfire disease - GUO Tao1, 2, WANG Hancheng2, YU Zhihe1*, CAI Liuti2, WANG Feng2*, CHEN Xingjiang2 (Guangxi Zhiwu)
The stability of phyllosphere microbial community is closely related to plant health. In order to understand the microecological characteristics of tobacco leaves infected with wildfire disease, community structure and diversity of phyllosphere microbiome in diseased spots and healthy tissues of tobacco leaves with different degrees of disease were analyzed using high-throughput sequencing technology in this paper. The results were as follows:(1)The dominant microorganisms in diseased and healthy tissues were Proteobacteria and Ascomycota, and their relative abundance in diseased tissues was significantly higher than that in healthy tissues. The dominant genera were Pseudomonas, Pantoea, Alternaria, Plectosphaerella and Conocybe, and only the relative abundance of Pseudomonas in diseased tissues was significantly higher than that in healthy tissues.(2)The diversity and richness of bacterial communities in diseased spots were higher than those in healthy tissues, and the diversity index showed a trend of decreasing and then increasing with the increase of the disease degree, and the richness index showed a trend of increasing and then decreasing. The richness and diversity index of fungal communities in diseased spots showed a trend of increasing and then decreasing with the increase of the disease degree, and the diversity index and richness of fungal communities in diseased spot tissues of mildly and moderately diseased leaves were higher than those in healthy tissues, but the diversity index and richness of fungal communities in heavily diseased tissues were lower than those in healthy tissues.(3)Gene functional information and relative abundance of bacteria in diseased spots and healthy tissues were generally similar, primarily were metabolism, genetic information processing and environmental information processing. The dominant functional taxa of fungus were plant pathogen, animal pathogen-endophyte-plant pathogen-wood saprotroph, undefined saprotroph, wood saprotroph and plant pathogen-wood saprotroph. The results provide a reference for the understanding of evolutionary pattern of tobacco wildfire disease and characterization of the phyllosphere microbial community.